Tutela jurisdicional dos interesses massificados: a indenização por dano moral coletivo como instrumento de combate ao dumping social - BAHIA, Camilla do Nascimento (2023)
The purpose of this monograph is to analyze social dumping and its consequences, in order to better understand it, as well as to investigate how national and regional jurisprudence faces the problem. In this regard, the work is structured based on bibliographic research, in a theoretical perspective, as well as in the qualitative and quantitative study of sentences handed down by the Regional Labor Court of the 8th Region, in an empirical perspective. To this end, at first, the influence of capitalism on the precariousness of labor relations and the concept of dignity as a protective mantle of the human being is demonstrated. Then, the origin and conceptualization of the term dumping are discussed in international and internal perspective. Afterwards, collective labor protection is presented as an adequate way to combat collective injuries resulting from social dumping. In sequence, the condemnation of supplementary compensation for collective moral damage is pointed out as a skillful instrument to punish the ofender, dissuade the repetition of similar conduct and compensate for the social damage caused by the practive of social dumping. Finally, the performance of the TRT-8ª Region is evaluated, based on the sentences handed down by the Court, with regard to the treatment of the institute. Based on this, it is argued that the supplementary compensation for collective moral damages, whose treatment must occur through collective judicial protection, is an effective method for combating social dumping, provided that it is arbitrated in a satisfactory amount and with a social destination, able to materialize the punitive, preventive-pedagogical and compensatory purposes of civil liability.